Preservatives in Pharmaceuticals: Are They Really Safe? - Kumar, Mohit; Chopra, Shruti; Mandal, Uttam K.; Bhatia, Amit (Current Drug Safety, 2023)
Preservatives are the ingredients that are utilized in order to improve the shelf life of products (Medicines, food). These tend to slow down or stop the degradation or decomposition processes, therefore, enhance the shelf life of the products. These agents either interfere with the chemical reaction or check the growth of microorganisms in the products. Preservatives are classified according to the mode of action or source or chemical nature. The preservation efficacy can be affected by various factors, e.g., interaction with other components, nature of preservatives, type of containers, type of micro-organism, and pH. Despite being vital for various types of products, these chemicals are not safe, if not used appropriately. The review will provide an updated detail of different types of preservatives along with their safety aspect. This review also highlighted the maximum safe concentration of preservatives that can be required to develop a formulation with maximum safety and low toxicity.
Keywords: parabens